2018
DOI: 10.3855/jidc.10171
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of circulating mononuclear cells in active pulmonary tuberculosis

Abstract: Introduction: Interpreting the interactions between M. tuberculosis and the host innate and adaptive immune defense mechanisms is mandatory for understanding the pathogenesis of active pulmonary TB (APTB). The aim was to describe the distribution of mononuclear cells in APTB and their relation to disease severity. Methodology: A case-control study of peripheral blood CD4+ T cells, CD8+ T cells, B-lymphocytes, NK cells, T regulatory lymphocytes (Tregs) and monocytes by flow cytometry. The patients had clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Previously, Elkholy et al. reported that the frequency of CD3-CD19+ B cell in peripheral blood from patients with active pulmonary tuberculosis was significantly lower than in a control group ( 47 ). In contrast, Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Elkholy et al. reported that the frequency of CD3-CD19+ B cell in peripheral blood from patients with active pulmonary tuberculosis was significantly lower than in a control group ( 47 ). In contrast, Wu et al.…”
Section: Discussionmentioning
confidence: 99%